Assessing the relationship between the ICT development and the achievement of the Sustainable Development Goals in Europe using regression models: policy implications - Jorge Perez Martinez; Felix Hernandez-Gil; Daniel Pe\~na (International Telecommunications Society (ITS), 2021)
The relationship between the implantation of Information and Communication Technologies (ICT) and the achievement of the Sustainable Development Goals (SDG), agreed at the United Nations is studied using regression models based on indicators on the SDG achievement and on the ICT adoption. The 17 SDG and their specific indicators are analyzed paying special tension to the European countries. Results shows a high positive association between the general SDG achievement and the ICT adoption. The aspects that benefit most clearly from digitization are those related to social and economic progress, including those such as poverty reduction, health care, quality of education and industry improvement. However, the study also shows that digitalization is associated to a poor achievement in areas related to the natural environmental preservation and climate change fight, including among them those related to electronic waste and greenhouse gas emissions. This is probably mostly due to the indirect effects.
Keywords: 330; Sustainable Development Goals; Information and Communication Technologies; Inclusive Internet Index; European Union